1992
DOI: 10.1161/01.hyp.19.4.301
|View full text |Cite
|
Sign up to set email alerts
|

A Ca(2+)-dependent K+ current is enhanced in arterial membranes of hypertensive rats.

Abstract: This study was designed to investigate the role and regulation of arterial membrane K + channels in hypertension. Aortic segments from normotensive Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHR) were suspended for isometric tension recording. In other experiments, proximal aortic segments (PS) (exposed to high pressure) and distal aortic segments (DS) (exposed to lower pressure) were removed from surgically coarcted Sprague-Dawiey rats and similarly prepared. Aortas from SHR and PS dose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 19 publications
(13 reference statements)
7
52
0
Order By: Relevance
“…This increase was detected only at positive membrane potentials and was not observed in the presence of LaCl 3 or TEA" 1 " or in cells in which the internal Ca 2+ level was clamped at zero. Thus, our results are consistent with the findings by Rusch et al, 16 who observed an enhanced whole-cell K + current in aortic smooth muscle cells from SHR after stimulation with the Ca 2+ ionophore A23187. However, we observed an increase in the absence of any pharmacologic intervention.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This increase was detected only at positive membrane potentials and was not observed in the presence of LaCl 3 or TEA" 1 " or in cells in which the internal Ca 2+ level was clamped at zero. Thus, our results are consistent with the findings by Rusch et al, 16 who observed an enhanced whole-cell K + current in aortic smooth muscle cells from SHR after stimulation with the Ca 2+ ionophore A23187. However, we observed an increase in the absence of any pharmacologic intervention.…”
Section: Discussionsupporting
confidence: 94%
“…These features are consistent with the observation of K + current. Similar to what was reported for vascular smooth muscle K + current, 16 this current reversed at -6 0 ± 2 mV at 5 mmol/L extracellular K + (n=5 to 6), as measured by its tail current. Comparison of the K + current-voltage relations between WKY and SHRSP cells was done by progressively increasing the test potential in 10-mV steps to +80 mV at a constant holding potential of -8 0 mV.…”
Section: Whole-cell K + Currentsupporting
confidence: 87%
See 1 more Smart Citation
“…DISCUSSION K Ca channels are gated by voltage and calcium and have various conductances and pharmacological sensitivities. The big conductance K Ca channels have been identified in many types of vascular smooth muscle cells (17)(18)(19)(20). The functioning of these K Ca channels controls membrane potential and affects vascular activity.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the activation of Ca2+-activated K+-channels could lead to vasodilatation. Rusch et al (1992) showed that a Ca2'-activated K+-current was enhanced in arterial membranes from genetic and experimental models of hypertensive rats. Asano et al (1993) showed that ChTX-sensitive Ca2+-activated K+-channels were highly activated in arteries from spontaneously hypertensive rats (SHR) as compared to normotensive rats.…”
Section: Introductionmentioning
confidence: 99%